Baris Memedi Dance in Jatiluwih Village Tabanan Bali: A Strategy to Preserve Traditional Arts - Dana, I Wayan; Artini, Ni Kadek Juni (Harmonia: Journal of Arts Research and Education, 2021)
The Baris Memedi dance depicts a group of ‘ghosts’ who live in haunted places such as graves, cliffs, and in large trees. It is danced by 7-15 male dancers. This dance is performed in Ngaben (cremation) ceremony called Pitra Yadnya, using the Baleganjur gamelan accompaniment. The objective of this study is  to analyze the form of existence of the Baris Memedi dance in implementing the Pitra Yadnya ceremony. Another objective is to understand the strategy for its preservation as a traditional art so that this dance can live and be long-lasting until today. The additional objective is to find the uniqueness of the dance that it needs preservation. The method used was a qualitative method that considers the issues of cultural context, ideology, interests, power in the culture, and meaning which refers to the culturalistic-humanistic paradigm, namely civilizing humans and humanizing humans. Based on observation, Baris Memedi dance has four stages in its presentation form. The preservation strategy is the active role of supporting the community, the role of Jatiluwih Village apparatus, Jatiluwih artists’ participation, and the government’s support. The most important aspect of Baris Memedi it is inseparable from its community. The proponents of traditional arts should continue to pursue these preservation efforts so that the arts have cultural resilience through Ajeg Bali.